PENGARUH MODEL PEMBELAJARAN CTL (CONTEXTUAL TEACHING AND LEARNING) TERHADAP KEMAMPUAN CRITICAL AND CREATIVE THINKING SISWA SMP - Arsyad, Arsyad; Safitriani, Safitriani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT The learning process in Indonesia continues to change to find effective strategies, but there are still many students who have low absorption of the material. This requires teachers to create active, creative learning and encourage students' critical thinking skills. This study aims to provide an overview of the level of influence of the CTL learning model on the creative and critical thinking skills of SMP N 16 Jambi City students. The approach used in this research is quantitative with the sampling technique is total sampling. The CTL learning model shows positive results on students' creative and critical thinking skills, with the category of